Russia - Akhmetova, Elmira (Brill, 2016)
Following the pattern of 2014, Muslims in Russia continued to focus on both their internal affairs and international diplomacy in 2015. The activities of the Soviet Muftiyev Rossii(Russian Council of Muftis, RCM), the most influential Islamic establishment in Russia, were centred on the opening of the Moscow Cathedral Mosque after its reconstruction, which began in 2011, was completed.